Multidisciplinary model to implement pharmacogenomics at the point of care - Caraballo, Pedro J.; Hodge, Lucy S.; Bielinski, Suzette J.; Stewart, A. Keith; Farrugia, Gianrico; Schultz, Cloann G.; Rohrer-Vitek, Carolyn R.; Olson, Janet E.; St. Sauver, Jennifer L.; Roger, Veronique L.; Parkulo, Mark A.; Kullo, Iftikhar J.; et al. (Genetics in medicine, 2017)
Despite potential clinical benefits, implementation of pharmacogenomics (PGx) faces many technical and clinical challenges. These challenges can be overcome with a comprehensive and systematic implementation model. The development and implementation of PGx were organized into eight interdependent components addressing resources, governance, clinical practice, education, testing, knowledge translation, clinical decision support (CDS), and maintenance. Several aspects of implementation were assessed, including adherence to the model, production of PGx-CDS interventions, and access to educational resources. Between August 2012 and June 2015, 21 specific drug–gene interactions were reviewed and 18 of them were implemented in the electronic medical record as PGx-CDS interventions. There was complete adherence to the model with variable production time (98–392 days) and delay time (0–148 days). The implementation impacted approximately 1,247 unique providers and 3,788 unique patients. A total of 11 educational resources complementary to the drug–gene interactions and 5 modules specific for pharmacists were developed and implemented. A comprehensive operational model can support PGx implementation in routine prescribing. Institutions can use this model as a roadmap to support similar efforts. However, we also identified challenges that will require major multidisciplinary and multi-institutional efforts to make PGx a universal reality. Genet Med19 4, 421–429.